Nora the mind reader - Gidali, Orit (Enchanted Lion Books, 2012)
"One day, Nora returns home from kindergarten upset because a boy in her class told her that she has the legs of a flamingo! When her mother gives her a magic wand to read people's minds, a new and fascinating world opens for her. She discovers that people don't always say what they think or think what they say"--